Girit Nizamnamesi'ne Göre (1868) Girit Adası'nın Adli ve İdari Teşkilatı - BURSALI, OSMAN SAFA (My University, 2022)
1860’larda Girit Adası’nda yaşanan siyasi ve toplumsal huzursuzluklara Avrupa devletlerinin müdahil olma çabalarına karşılık olarak Osmanlı idarecilerinin ortaya koyduğu ıslahat girişimleri içinde Girit Nizamnamesi’nin (1868) önemli bir yeri bulunmaktadır. Dönemin padişahı Abdülaziz’in görevlendirdiği sadrazam Âli Paşa 1867 yılının sonbahar aylarında adaya gelerek genel af ilan edildiğini açıklamıştır. Buna binaen Girit olaylarında rol alan toplumsal grupların temsilcilerinden oluşan bir heyetle yaptığı görüşmelerden sonra Âli Paşa, nizamnamenin yayımlanmasına ön ayak olmuştur. Nizamname, adanın gerek idari gerekse adli teşkilatının yapısına ve bu teşkilatın görev ve yetkilerine dair maddeler içermektedir. Nizamnamenin baş tarafında ada sakinlerine bazı ekonomik avantajlar sağlayacak düzenlemeler zikredildikten sonra adanın genel idaresine ilişkin hususlar sıralanmaktadır. Vali, adayı Osmanlı idaresinin genel kanunları yanında adaya mahsus kanunlarla yönetir. Ada idari olarak livalara bölünür, her birinin başında mutasarrıf bulunur. Mutasarrıfların yarısı Müslüman yarısı Hıristiyan’dır. Vilayet, liva ve kaza nezdinde idare meclisleri bulunur. Vali başkanlığındaki vilayet idare meclisinde valinin iki müşaviri ile hâkimlerin müfettişi, adadaki metropolit, defterdar, mektupçular, halktan seçilmiş üç Müslüman ve üç Hıristiyan üye bulunur. Liva idare meclisinde mutasarrıf başkanlığında onun yardımcısı ile hâkim, livadaki piskopos, muhasebeci, tahrirat başkatibi ile halktan seçilmiş üç Müslüman ve üç Hıristiyan üye bulunur. Livada yalnızca Hıristiyan halk varsa üyelerin altısı da Hıristiyan’dır. Vilayet, liva ve kazalarda kişilerarası ilişkiler ve cinayete ilişkin davaların görülmesi için dava meclisleri bulunur. Vilayet merkezinde Müslümanlar arasında meydana gelen uyuşmazlıkların çözümü için bir şer’î mahkeme bulunur. Köylerde birer tane, sancaklarda ise Müslüman ve Hıristiyanlar için ayrı birer tane halk tarafından seçilmiş ihtiyar meclisi (dimoyrondiya) bulunur. Vilayet çapında teşkil edilen Meclis-i Umumide her kazadan iki üye bulunur. Bu meclisin müzakereye yetkili olduğu konular arasında bayındırlık, ticaret, tarım, sanayi, eğitim ve adadaki huzuru sağlaması beklenen sair ıslahat konuları bulunmaktadır. Nizamname, dava ve ihtiyar meclisleri ile ticaret mahkemelerinin teşkili ve görevlerine ilişkin yetmiş yedi madde; idare meclislerinin teşkili ve görevlerine ilişkin kırk dört madde ve Meclis-i Umuminin teşkili ve görevlerine ilişkin otuz dört madde içermektedir. Bu tebliğde, son dönem Osmanlı idare ve anayasa hukuku alanındaki gelişmelerin genel çerçevesi içinde Girit Nizamnamesi’nde öngörülen adli ve idari ıslahat tanıtılacak ve değerlendirilecektir.

The Nizamname of Crete (1868) has an important place among the reform initiatives put forward by the Ottoman administrators in response to the efforts of the European states to intervene in the political and social unrest on the island of Crete in the 1860s. Grand Vizier Âli Pasha, who was appointed by the sultan of the period, Abdülaziz, came to the island in the autumn of 1867 and announced that a general amnesty was declared. Accordingly, after his meetings with a delegation consisting of representatives of the social groups involved in the Cretan events, Âli Pasha initiated the publication of the nizamname. The regulation contains articles on the structure of both the administrative and judicial organization of the island and the duties and authorities of this organization. After mentioning the laws that will provide some economic advantages to the island residents at the beginning of the nizamname, the issues related to the general administration of the island are listed. The governor rules the island with the general laws of the Ottoman administration as well as the laws specific to the island. The island is administratively divided into livas, each of which is headed by a mutasarrıf. Half of the mutasarrıfs are Muslim and half Christian. There are administrative councils in the province (vilayet), liva and county (kaza). In the provincial administrative council chaired by the governor, there are two advisors of the governor and the inspector of the judges, the metropolitan on the island, the treasurer, the letter writers, three Muslim and three Christian members elected from the people. In the liva administrative council, there are three Muslim and three Christian members elected from the people, under the chairmanship of the mutasarrıf, with his deputy and the judge, the bishop in the liva, the accountant, the tahrirat clerk. If there are only Christian people in the liva, all six of the members are Christians. There are case assemblies in the province, livas and counties to hear cases related to interpersonal relations and murder. There is a shar’i court in the center of the province for the settlement of disputes between Muslims. There is one council of elders (dimoyrondia) elected by the people for Muslims and Christians in each of the villages and in the sancaks. There are two members from each county in the General Assembly, which is formed throughout the province. Among the issues that this assembly is authorized to negotiate are public works, trade, agriculture, industry, education and other reform issues that are expected to ensure peace on the island. The nizamname contains seventy-seven articles pertaining to the organization and duties of the case assemblies, councils of elders, and commercial courts; forty-four articles on the organization and duties of administrative councils and thirty-four articles on the organization and duties of the General Assembly. In this paper, the judicial and administrative reforms envisaged in the Nizamname of Crete will be introduced and evaluated within the general framework of the recent developments in the field of Ottoman administrative and constitutional law.
Keywords: Sosyal ve Beşeri Bilimler; Hukuk; Hukuk Tarihi; Social Sciences and Humanities; Law; History of Law; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; KANUN; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; LAW; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities